Knowledge and practices of oral hygiene among undergraduate students of dayalbagh educational institute, Agra - Suman Madan; Richa Verma; Gul Mathur (Wolters Kluwer Medknow Publications, 2021)
Background: Healthy and well-functioning teeth in all phases of life is a necessity. Teeth help in proper mastication of food as well as in word pronunciation. It gives fullness to the face, thereby helping in the social appearance of a person. Oral health and systemic health are interconnected. Past studies indicate that oral diseases cause or increase the severity of noncommunicable diseases. The general public is unaware of this connection. Thus, the present research work was planned to assess the oral hygiene practices of students and their awareness for maintenance of oral health. Research Methodology: The present survey was conducted among 510 students (135 boys and 335 girls) in the age group of 17-30 years studying in Dayalbagh Educational Institute. Data were collected through a questionnaire adapted from the standard tool of oral health questionnaire by the WHO. Results and Discussion: The result of the present study showed that 93% of the students were using toothpaste and toothbrush for cleaning teeth, but only 31% and 2% of the students were using other measures such as mouthwash and floss. Data also showed that only 44% of the students brush twice a day and only 27% visit dentist for routine checkup. Conclusion: Majority of the students were aware of the linkage between oral health and systemic health. Thus, it is essential to organize oral health education program at mass level to create awareness in public so that not only their oral health but also their general health can be improved.